Pelatihan Pembuatan Buku Ajar Berbasis Canva Pada Guru MGMP IPA Kabupaten Keerom, Papua. - Satar, Suriyah; Nurbaya, Nurbaya; Listiani, Hanida; Lodeh, Cartika Candra (Universitas Cenderawasih, 2024)
The development of digital technology has brought significant changes to the world of education, especially in the delivery of teaching materials. Canva provides an easy-to-use platform for creating interesting and interactive teaching materials. In this context, Canva-based textbook creation training is important for teachers, especially those who are members of the Keerom Regency Science MGMP, to improve their skills and educational effectiveness. The training took place over several sessions, including an introduction to Canva, textbook prototyping, interactive content preparation, and design review. The training participants were 30 science teachers who were members of the Keerom Regency Science MGMP from various schools. Data was collected through pre- and post-test questionnaires to measure participants' advanced knowledge and skills when using Canva. The teachers' knowledge of the Canva application before the training was only 6 teachers who were at a good and very good level, and after completing the training, all 30 teachers were at a good and very good level, knowing about the Canva application in the form of graphic design applications, especially for making textbooks..